2015 IEEE International Conference on Robotics and Automation (ICRA) 2015
DOI: 10.1109/icra.2015.7139805
|View full text |Cite
|
Sign up to set email alerts
|

Smooth stabilisation of nonholonomic robots subject to disturbances

Abstract: In this paper, we address the problem of stabilisation of robots subject to nonholonommic constraints and external disturbances using port-Hamiltonian theory and smooth time-invariant control laws. This should be contrasted with the commonly used switched or time-varying laws. We propose a control design that provides asymptotic stability of an manifold (also called relative equilibria)-due to the Brockett condition this is the only type of stabilisation possible using smooth time-invariant control laws. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the literature, several control techniques have been developed for stabilization of nonholonomic systems. Some of these include discontinuous time-invariant techniques [5][6][7][8], time-varying techniques [9][10][11][12], adaptive techniques [13,14], and sliding mode control technique [15][16][17][18][19][20]. Sliding mode control (SMC) is a special nonlinear control technique.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, several control techniques have been developed for stabilization of nonholonomic systems. Some of these include discontinuous time-invariant techniques [5][6][7][8], time-varying techniques [9][10][11][12], adaptive techniques [13,14], and sliding mode control technique [15][16][17][18][19][20]. Sliding mode control (SMC) is a special nonlinear control technique.…”
Section: Introductionmentioning
confidence: 99%
“…Remark Standard IDA‐PBC has been applied in References 3,24 to stabilize a manifold containing the desired equilibrium point, in the latter publication including disturbance rejection. In References 8,25 switched or nonsmooth versions of IDA‐PBC that ensure convergence to the desired equilibrium point are proposed.…”
Section: Regulation Of Nonholonomic Systems Via Epd Ida‐pbcmentioning
confidence: 99%
“…It is shown that an infinite predictive horizon can guarantee stability of a system, but the choice of an infinite predictive horizon may not be feasible for a nonlinear system in practice. 23 One of the first surveys dealing with nonholonomic control problems was written by Kolmanovsky and McClamroch. 51 In the survey, the authors mention two problems (motion planning control systems and feedback stabilization) and point out three other important issues: models of nonholonomic control systems, new control approaches for motion planning for nonholonomic systems, and stabilization of these new approaches.…”
Section: Model Predictive Control Approachesmentioning
confidence: 99%
“…Moreover, the main issues, including stability and safety, are also discussed using the Brockett stability theory. 23 An approach based on Linear Matrix Inequalities (LMI) is proposed by Araújo et al 7 in 2011. The authors present a methodology for state feedback MPC synthesis applied to the trajectory tracking control problem of a three-wheeled omnidirectional mobile robot.…”
Section: Stabilitymentioning
confidence: 99%